Gas breakdown in DC electric field in a discharge tube with flat and conical cathodes - Lisovskiy, V.A.; Osmayev, R.O.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2014)
This paper reports dc breakdown curves we registered between a flat anode and cathodes of various design: a flat one and cones of different height; the least inter-electrode distance was kept constant. We observed that the minima and the right-hand branches of breakdown curves coincided practically whereas the left-hand ones did not. At lower pressure values a divergence of left-hand branches of breakdown curves was registered for cathodes of different design. For conical cathodes the breakdown occurs either near its sharp tip or at the lateral surface of the cone at some distance from its tip.